Effect of addition of effective microorganisms on chemical and rumen fermentation characteristics of wheat straw treated with four levels of urea - Elobied, G.H.; Yousif, M.T.; Abdalla, I. A. (Gezira Journal of Agricultural Science; Vol 11 No 1 (2013), 2013)
An experiment was conducted in the laboratories of chemistry and biology, University of Gezira, to find the effects of effective microorganisms (EM) on chemical and in vitro rumen fermentation characteristics of ammoniated wheat straw on April 2011. Wheat straw was treated with four levels of urea (0, 2, 4 and 6%). Two sets of three replicates each were used. To one set EM was added, while the other one which included no EM was used as a control. It was found that addition of EM increased the urea nitrogen fixed in the straw. CP (crude protein) increased while CF (crude fiber) decreased with increasing levels of urea. The corresponding levels with added EM showed more increase in CP and a decrease in CF, though it was not significant (P>0.05). However, at higher urea levels, the straw was significantly (P<0.05) improved in terms of increased CP and decreased CF. The DM (dry matter), OM (organic matter), CP and CF digestibilities were improved with increasing levels of urea and it was substantially increased with addition of EM. Rumen fluid pH tended to increase with the increasing levels of urea in both the control and the treatment. Rumen NH 3 -N increased significantly (P<0.05) at 4% and 6% levels in treatments which included  EM and at 6% level in ammoniated straw without EM. Also, there was a trend of increasing total protozoal count with inclusion of EM but this was not significant (P>0.05). It could be concluded that inclusion of EM to ammoniated wheat straw improved both the chemical and the in vitro rumen fermentation of wheat straw and reduced urea–N lost to the atmosphere.